Perinatal complications in patients with unisutural craniosynostosis: An international multicentre retrospective cohort study. Issue 11 (November 2017) - Cornelissen, Martijn J.; Söfteland, Madiha; Apon, Inge; Ladfors, Lars; Mathijssen, Irene M.J.; Cohen-Overbeek, Titia E.; Bonsel, Gouke J.; Kölby, Lars
Abstract: Purpose: Craniosynostosis may lead to hampered fetal head molding and birth complications. To study the interaction between single suture craniosynostosis and delivery complications, an international, multicentre, retrospective cohort study was performed. Materials and methods: All infants born between 2006 and 2012 in the Netherlands and Sweden with sagittal or metopic suture synostosis were included. All births were included as a reference population. The primary outcome measure was rate of medically assisted labor. The secondary outcomes included method of conception, term of birth and fetal position. Results: We included 152 trigonocephaly patients, 272 scaphocephaly patients and 1.954.141 controls. A higher rate of assisted reproductive technology (ART) was found in patients with trigonocephaly (13%) and scaphocephaly (7%) compared to controls (3%, p < 0.001). Scaphocephaly resulted in more postterm births (8% vs 4%, p < 0.001). Trigonocephaly patients showed more preterm births (11% vs 6%, p < 0.001), breech position was more frequent (10% vs 4%, p = 0.003) and labor was more often induced. Rate of assisted delivery, including cesarean section, was significantly higher in both patient groups. Conclusions: Scaphocephaly leads to more postterm births and an increased rate of cesarean sections. Trigonocephaly is related to ART, and in addition higher rates of breech position and cesarean section are found. Prenatal detection of single suture craniosynostosis could improve perinatal care.